Rút gọn A=(x/x^2-4 + 2/2-x + 1/x+2) * x+2/2

Rút gọn
A=(x/x^2-4 + 2/2-x + 1/x+2) * x+2/2

2 bình luận về “Rút gọn A=(x/x^2-4 + 2/2-x + 1/x+2) * x+2/2”

  1. ĐKXĐ: x \ne 2,x \ne -2
    Ta có: A = (x/(x^2 – 4) + 2/(2 – x) + 1/(x + 2)) . (x + 2)/2
    => A = (x/((x -2)(x + 2)) – 2/(x – 2) + 1/(x+ 2)) . (x + 2)/2
    => A = (x/((x – 2)(x + 2)) – (2(x + 2))/((x – 2)(x + 2)) + (x – 2)/((x -2)(x + 2)) . (x + 2)/2
    => A = (x  – 2x – 4 + x – 2)/((x -2 )(x + 2)) .(x + 2)/2
    => A = (-6)/((x – 2)(x + 2)) . (x + 2)/2
    => A = (-3)/(x – 2)
    => A = 3/(2 – x)
    Vậy A =3/(2 – x) với x \ne 2,x \ne -2
    $#duong612009$

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    A=(x/(x^2-4)+2/(2-x)+1/(x+2))*(x+2)/2(ĐKXĐ:x\ne±2)
    A=(x/(x^2-2^2)-2/(x-2)+1/(x+2))*(x+2)/2
    A=(x/((x-2)(x+2))-(2(x+2))/((x-2)(x+2))+(x-2)/((x+2)(x-2)))*(x+2)/2
    A=(x/((x-2)(x+2))-(2x+4)/((x-2)(x+2))+(x-2)/((x+2)(x-2)))*(x+2)/2
    A=(x-2x-4+x-2)/((x-2)(x+2))*(x+2)/2
    A=(-6)/((x-2)(x+2))*(x+2)/2
    A=(-6(x+2))/(2(x-2)(x+2))
    A=(-3)/(x-2)
    A=3/(2-x)
    Vậy A=3/(2-x) với ĐKXĐ:x\ne±2

    Trả lời

Viết một bình luận

Câu hỏi mới